New efficient tetraphenyl silylated poly(azomethine)s based on "pincer-like" bis(imino)pyridine iron(III) complexes as heterogeneous catalysts for CO2 conversion. (5th March 2020) - Sobarzo, Patricio A.; Terraza, Claudio A.; Maya, Eva M.
Graphical abstract: Highlights: New poly(azomethine)s based on bis(imino)pyridine pincers and tetraphenylsilane groups. High thermally stable supports very effective for iron (III) anchoring. Efficient heterogeneous catalysts for cycloaddition of CO2 to epoxides, high TONs. Heterogeneous catalysts work in softer conditions than reported for similar catalysts. Recyclable and stable catalysts without iron leaching. Abstract: Aromatic poly(azomethine)s containing simultaneously for the first time both tetraphenyl silane moeties and "pincers" of bis(imino)pyridine were prepared, to provide these polymers with a robust structure and ability to anchor metals. The polymers were prepared from difunctional monomers which provide an special conformation yielding moderate surface areas (up to 60 m 2 /g). The insolubility and further incorporation of iron to these polymers have generated a new set of heterogeneous catalysts with high metal content, high thermal stability and with excellent catalytic performance in the cycloaddition of CO2 to epoxides to form cyclic carbonates. Very small amounts of catalysts work efficiently, in the absence of solvent, at moderate CO2 pressures (3 bar) showing very high yields of epoxide conversion (up to 95%), 100% of selectivity to the corresponding cyclic carbonate in all cases and high turn-over numbers (up to 7000) being reused at least five times with no apparent loss in catalytic activity. The new catalysts are more efficient than a similar catalyst previously reported for this conversion and work in milder conditions.